2015
DOI: 10.1136/bmjopen-2014-006189
|View full text |Cite|
|
Sign up to set email alerts
|

Overweight and obesity on the island of Ireland: an estimation of costs

Abstract: ObjectivesThe increasing prevalence of overweight and obesity worldwide continues to compromise population health and creates a wider societal cost in terms of productivity loss and premature mortality. Despite extensive international literature on the cost of overweight and obesity, findings are inconsistent between Europe and the USA, and particularly within Europe. Studies vary on issues of focus, specific costs and methods. This study aims to estimate the healthcare and productivity costs of overweight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 21 publications
3
52
0
1
Order By: Relevance
“…39,40 In NI, measured obesity rates in adults also increased with time, from less than 10% in women aged 16 to 64 years in 1992 41 to 22% in 2013. 42 Corresponding rates in Israel were 13% in 2000 and 16% in 2013. 43 Genetic factors such as BRCA1/2 mutations increase the risk of ovarian cancer (especially BRCA2).…”
Section: Incidence Trendsmentioning
confidence: 99%
“…39,40 In NI, measured obesity rates in adults also increased with time, from less than 10% in women aged 16 to 64 years in 1992 41 to 22% in 2013. 42 Corresponding rates in Israel were 13% in 2000 and 16% in 2013. 43 Genetic factors such as BRCA1/2 mutations increase the risk of ovarian cancer (especially BRCA2).…”
Section: Incidence Trendsmentioning
confidence: 99%
“…The three studies with HCA/FCA ratios <2 all measured short-term sick leave [7072]. Other studies that only assessed short-term sick leave likewise typically reported modest HCA/FCA cost ratios [73]. Conversely, all nine studies that reported ratios ≥19 included productivity costs from either premature mortality or long-term disability in the HCA estimates.…”
Section: Applicationsmentioning
confidence: 99%
“…Of the six studies in Table 1 that addressed the burden of cancers, the four that included mortality costs had HCA/FCA ratios that were mostly between 24 and 48 [31, 33, 74, 75], whereas the two studies that only considered morbidity costs had ratios of 2.6 and 3.9 [76, 77]. The fact that four studies that included mortality costs reported HCA costs less than 10-fold higher than FCA estimates likely reflects at least in part the focus of those studies on conditions or exposures with low mortality rates among working-age adults, specifically obesity [73, 78, 79], injuries [80], and smoking [81]. …”
Section: Applicationsmentioning
confidence: 99%
“…In 2011 it was reported that absenteeism due to illness was costing Irish businesses €1·5 billion per year (€818 per employee per year) ( 4 ) . Furthermore, productivity loss due to overweight and obesity was estimated at €865 million in 2009 in Ireland, with absenteeism identified as the main driver ( 5 ) . In an effort to curtail this cost escalation, workplace health promotion has moved to the forefront of organisational agendas.…”
mentioning
confidence: 99%